Effectiveness of a Proposed Training Program for Grade 11 Chemistry Teachers to Acquire Chemistry Conceptual Problem Posing and Solving Skills - Mohammed K. Al- Sinani; Abdullah K. Ambusaidi (Sultan Qaboos University, 2018)
The aim of the current study was to investigate the effectiveness of a proposed training program for grade 11 chemistry teachers to enhance their chemistry conceptual problem posing and solving skills. The sample was based on one group of sixteen chemistry teachers from various schools in the Dakhelyah Governorate of the Sultanate of Oman. They were ponded training in a three day workshop on how to pose and solve chemistry conceptual problems, by using  the proposed strategies suggested by the researchers. Pre and post chemistry conceptual problem posing and solving tests were applied to the sample of the study designed by the researchers. The results demonstrated statistically significant differences at ( α= 0.05) on chemistry conceptual problem posing and solving skills, among chemistry teachers between pre and post tests in favor to post tests. Recommendations and suggestions were provided based on the findings.